PARADIGMA KRITIS DAN AKSIOLOGI DALAM PENGEMBANGAN MANAJEMEN KEINGINAN DI LEMBAGA BISNIS - Rahayu, Elly; Kifti, Wan Mariatul; Muti'ah, Rahma; Mujiatun, Siti (Smart Education, 2026)
Abstract: This riset conceptually explores the analysis of power structures in the management of desires inside modern business organizations via the lens of critical paradigms and how axiological principles such as justice, sustainability, and autonomy might steer business practices towards enhanced ethicality and introspection. The critical paradigm method aims to